2019
DOI: 10.3389/fendo.2019.00462
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics for the Identification of Biomarkers in Testicular Cancer–Review

Abstract: A large number of biomarkers have been proposed for the diagnosis of testicular cancer, representing putative molecular targets for anticancer treatments. However, no conclusive data have been provided. Proteomics represents a research field recently developed. It evaluates the large-scale analysis of the full protein components of a single cell, of a specific tissue, or of biological fluids. In the last decades, proteomics has been applied in clinical fields, thanks to modern technology and new bioinformatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
0
13
0
2
Order By: Relevance
“…With the advent of omics, a few proteomic studies have been conducted using testicular tissue samples to identify potential markers for early diagnosis and monitoring of TC [99][100][101]. Recently, Milardi et al reported that tumor markers AFP, hCG, and LDH can be used in the clinical management of testicular germ cell tumors [102].…”
Section: Protein Profiling In Testicular Cancermentioning
confidence: 99%
“…With the advent of omics, a few proteomic studies have been conducted using testicular tissue samples to identify potential markers for early diagnosis and monitoring of TC [99][100][101]. Recently, Milardi et al reported that tumor markers AFP, hCG, and LDH can be used in the clinical management of testicular germ cell tumors [102].…”
Section: Protein Profiling In Testicular Cancermentioning
confidence: 99%
“…Moreover, studies in proteomics, especially taking advantage of technologies such as mass spectrometry, may bring further novelty to the field [ 169 ]. In fact, most proteomic-based studies in this area have focused on tissues instead of liquid biopsies and have disclosed putative biomarkers up- or down-regulated in specific histological subtypes, such as GSTM3, GCP6, CDK10, STARD7, DMTR1, PIWIL1, TMPRSS12 and PAK4, most being implicated in cell cycle regulation, apoptosis, and metabolism [ 170 , 171 , 172 , 173 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Essas biomoléculas possuem três vertentes de aplicações, sendo indicadas como biomarcadores preditivos, oferecendo informações sobre os riscos de um indivíduo contrair uma doença; biomarcadores de diagnóstico, quando é capaz de identificar a ocorrência de uma doença, e; biomarcadores de prognóstico, quando indica a forma como uma doença pode evoluir (Mayeux, 2004). Na pesquisa clínica, é recorrente o uso de biomarcadores, sobretudo na reumatologia, câncer, Alzheimer, doenças genéticas em geral e doenças infecciosas como leishmaniose e doença de chagas (Milardi et al, 2019).…”
Section: Fisiopatologiaunclassified